1982
DOI: 10.1007/bf01870882
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of L antibody with low potassium-type sheep red cells: Resolution of two separate functional antibodies

Abstract: Antibodies of two specificities in alloimmune sheep anti-L sera, anti-Lp and anti-L1, were separated by a new technique and characterized. Absorption of anti-L serum with trypsinized LK(LL) sheep red cells left anti-Lp antibodies; the absorbed anti-L1 antibodies were then eluted. Anti-Lp was only weakly lytic in the presence of complement; it had no effect on passive K influx, but stimulated active K influx. The stimulation could be reversed by eluting the antibody in glycine buffer at low pH. Stimulatory acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

1986
1986
2003
2003

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 23 publications
1
12
1
Order By: Relevance
“…The absorbed serum contained anti-Lb; adsorbed anti-Lb was then eluted from the trypsinized cells using an isotonic medium at pH 3 3 containing glycine-HCl. This method will be described in detail elsewhere (Smalley, Tucker, Dunham & Ellory, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…The absorbed serum contained anti-Lb; adsorbed anti-Lb was then eluted from the trypsinized cells using an isotonic medium at pH 3 3 containing glycine-HCl. This method will be described in detail elsewhere (Smalley, Tucker, Dunham & Ellory, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…A very high furosemide or bumetanide concentration (about 2 mM) is required for 50% inhibition [63]. The K + flux in LK sheep red cells is inhibited by anti-L 1 , a specific component of an antiserum against LK sheep red cells [297]. The K + flux must involve a small number of transport sites, since there are only about 850 anti-L binding sites per cell [297], or else the effect of anti-L 1 must be highly cooperative or mediated through a second messenger.…”
Section: Sheep Red Cellsmentioning
confidence: 98%
“…The K + flux in LK sheep red cells is inhibited by anti-L 1 , a specific component of an antiserum against LK sheep red cells [297]. The K + flux must involve a small number of transport sites, since there are only about 850 anti-L binding sites per cell [297], or else the effect of anti-L 1 must be highly cooperative or mediated through a second messenger. The number of cot ran sport sites may even be an order of magnitude lower than the number of antigen sites [297].…”
Section: Sheep Red Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results consistently show L activity associated with a 25 kDa polypeptide in LK red cells. Anti-L alloantisera has been divided into two activities; pump-stimulating activity (termed Lp) and KCl cotransport-inhibiting activity (termed Ll), this latter activity also showing strong complement binding (Smalley et al 1982). By sensitizing LK cells with an anti-L known to have strong Lp, but weak Ll, activity we have demonstrated that the 25 kDa polypeptide is recognized by the pump-stimulating Lp antiserum and therefore conclude that this glycoprotein is involved in sodium pump inhibition in LK sheep red cells.…”
Section: P Bristol Meeting 9-10 Februar Y 1990mentioning
confidence: 99%